ANALYSIS OF TRANSACTION COSTS AND BORROWER'S PERCEPTIONS COMPARISON TOWARD LOAN PROCEDURES IN FINANCIAL INSTITUTIONS IN RIMBA MELINTANG SUB-DISTRICT ROKAN HILIR REGENCY - Cyntiana Tetsa Putri; Ahmad Rifai; Kausar Kausar (JIP ( Jurnal Industri dan Perkotaan ), 2021)
Poverty is one of the basic problems that Indonesia is still facing. In response to this, the government issues a policy to improve the economic capacity of the community, through financial institutions as a source of capital. Financial institutions have different goals and motivations, so they have some differences in the determination of lending procedures and transaction fees applied, which will affect the perceptions of borrowers. This research is conducted at the BRI financial institution and Sharia Cooperatives (BMT AGROMADANI) in Rimba Melintang Sub-district, Rokan Hilir Regency. This study aims to: First, to identify lending procedures. Second, to analyze the comparison of the amount of transaction costs. Third, to analyze the perception of the borrower. This study uses a survey method with the sampling technique used is purposive sampling and the number of samples used in this study as many as 10 borrowers taken from each of the financial institutions. The results of the study explain that the more procedures or stages that are applied, the financial institutions will take longer to process loan or financing activities. BRI financial institution is more efficient in determining transaction costs incurred by borrowers of Rp. 559,800, compared to the Sharia Cooperative financial institution (BMT AGROMADANI) of Rp. 1,298,000. The average variable of borrowers' perceptions of lending procedures in BRI financial institution is in the score range of 93.66 with very good assessment criteria, while the Sharia Cooperative financial institution (BMT AGROMADANI) is in the score range of 81.66 with good assessment criteria.